Analysis of Dicionário da Língua de Sinais do Brasil: a Libras em suas mãos - D’Azevedo, Rodolpho Pinheiro (The ESPecialist, 2023)
This article presents the analysis of the Dicionário da Língua de Sinais do Brasil: a Libras em suas mãos by Capovilla et al. (2019). It is the most relevant and widespread Libras dictionary in the country, being the most recent version of the dictionaries produced by Capovilla’s team. This study is part of the doctoral research in Letters at the Federal University of Rio Grande Sul. The aim of this work is to analyze the dictionary in its constitutive components, in order to identify the paths and challenges for writing the dictionary of our research. As a methodology, we apply in this study the principles of canonical structuring for semasiological dictionaries (macro, microstructure, and Front Matter) from Borba and Bugueño-Miranda (2012), Bugueño-Miranda (2007), Bugueño-Miranda and Farias (2013) and Seliste (2019). As a result, we recognized the need to better define the essential features of the work, such as the user profile and its function, in order to structure the canonical components according to the real needs of potential users.